Perlindungan Konsumen dan Tanggung Jawab Perseroan Terbatas dalam Sengketa Layanan Transportasi Online Menurut Putusan MK No. 41/PUU-XVI/2018 - Dominique Oey Joylin (Jurnal Riset Multidisiplin Edukasi, 2025)
The development of digital technology has transformed the way society interacts socially and economically, including in the field of transportation, which is currently largely served by Limited Liability Companies through online applications such as Gojek and Grab. This study aims to examine the forms of consumer protection and the legal responsibilities of Limited Liability Companies in online transportation services, referring to Law Number 8 of 1999 concerning Consumer Protection and Constitutional Court Decision Number 41/PUU-XVI/2018. The method used is normative juridical with an approach that includes legislation, concepts, and case studies. The research findings indicate that although the Consumer Protection Law provides a legal basis for consumer protection, its implementation in the field shows an imbalance of responsibilities, where companies often evade accountability by placing the blame on driver partners. Constitutional Court Decision No. 41/PUU-XVI/2018 emphasizes that the providers of transportation services Online platforms not only function as technology mediators but also must be legally responsible for the losses suffered by consumers. Therefore, regulatory alignment between the Consumer Protection Law (UUPK), the Electronic Information and Transactions Law (UU ITE), and the Limited Liability Company Law (UU PT) is necessary to create justice, legal certainty, and effective consumer protection in the digital economy era.